(3JQLeGf GdReGf aj JQGLe GdCYjGfs - (3EHQGgje Hf eMeO Hf CjOeQ GdYdGFj GdSQGLj, GHf ObeGb , UGQe GdOjf ,J (B809 (3g` s
(3ChdgG (B:s
(3jHJOF HYjO GdhOhO Hf YHO GdQMef Hf Ydi Hf YHO Gdedc GdgdGdi s
(3BNQgG (B:s
(3jfJgi HBNQ JQLeI Ydi Hf jMji Hf aVd Gddg GdbQTi GdYOhi GdYeQi fGXQ OjhGf GddEfTGA s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B86s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B89 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs